THE IMPORTANCE OF WOMEN’S ROLE IN DIPLOMATIC RELATIONS - F. Karimova (Scholar Express Journal, 2023)
Women have long played an important role in diplomacy, but their efforts are often underestimated. It is time to acknowledge and celebrate the ways in which women are breaking down barriers and making a difference in diplomacy. This article will discuss the role of women in diplomatic relations
Keywords: diplomatic relations; gender equality; policymaking